The Finnish Academic Profession’s Divided Opportunities in Management and Governance - Aarrevaara, Timo; Ryynänen, Sanna; Tenhunen, Ville; Vasari, Pekka (Acta Paedagogica Vilnensia, 2021)
Finnish higher education consists of research-oriented universities and teaching-oriented universities of applied sciences, and both sectors have a role in research, development and innovation. This paper focuses on governance and management at the institutional and academic unit levels, based on responses to several questions in the APIKS survey regarding the influence of academics, performance targets of academic units and the influence of academics in decision making and workload. Institutions in both sectors of Finnish higher education emphasise strategies and are heavily reliant on public funding. Both sectors also have an orientation to strong performance management.
Keywords: academic profession; governance; influence; working conditions